GEOTURISM IN CAÇAPAVA DO SUL (RS, BRAZIL): PROPOSAL OF INTERPRETIVE PATHWAYS IN THE GUARITAS DO CAMAQUÃ (Terr@ Plural, 2021)
The main goal of this research was to identify, evaluate, and describe the points that illustrate the more representative geodiversity elements of the ‘Guaritas do Camaquã’ geosite, in Caçapava do Sul (south-central Rio Grande do Sul / Brazil). Eleven points attesting the geological-geomorphological evolution were selected, as well as points demonstrating the relationship between geodiversity and biodiversity present in the geosite. The points are connected along a system of four interpretive trails or pathways with different levels of difficulty. This research aims at contributing to the development of geotourism in Caçapava do Sul as one of the necessary actions in territories which aspire to become a UNESCO-certified Global Geopark.
Keywords: Geodiversity. Geoconservation. Geopark.